Desain Sistem Multimedia Interaktif Berbasis Gesture untuk Penggunaan dalam Lingkungan Smart Classroom - Muhammad Rhamadani; Tata Sutabri (JOURNAL SAINS STUDENT RESEARCH, 2025)
The development of technology in the world of education has encouraged the birth of various innovations in the learning process. One promising technology is the use of interactive multimedia systems based on gestures that can improve interaction between teachers and students in a smart classroom environment. This study aims to design and develop a multimedia system that can be controlled using hand movements (gestures), thus creating a more dynamic and interactive learning atmosphere. The research method used is Research and Development (R&D) with a prototyping model. The results of the study showed that the developed system was able to respond to gestures with 92% accuracy and significantly increase student engagement. This system is expected to be an innovative solution for more adaptive and enjoyable learning.